Harry [surname unknown] correspondence - Harry, active 1861.
ALS (1861 October 10; Portland, [Me.]) from Harry to his fiancée in Canada discussing the risk of imprisonment for those who criticized government policies during the Civil War. Other topics include his opinion of Yankee women and personal affairs.
British businessman residing in New England.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Women -- United States; Maine -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Public opinion; Businessmen